2020
DOI: 10.1108/amhid-07-2018-0032
|View full text |Cite
|
Sign up to set email alerts
|

“When other people try to understand”: exploring the experiences of people with intellectual disabilities, who also have mental health problems

Abstract: Purpose Recent guidelines from the National Institute of Health and Care Excellence highlight that service users (SUs) with intellectual disabilities and co-occurring mental health problems rarely get the opportunity to share their experiences of mental health services. Over the past 20 years, policy documents have stated that these individuals (SUs) must be included in decisions about their care. Research suggests that often this is not the case. Therefore, this paper aims to create a space for SUs to share t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…In light of this, we conducted a service evaluation study to explore the accessibility and prospective acceptability of videoconference-mediated psychological therapy with people with an ID. This evaluation is in line with the growing need of involving individuals with ID in decisions regarding their own care (Mattock, Beard & Baddeley, 2020).…”
Section: Introductionsupporting
confidence: 57%
“…In light of this, we conducted a service evaluation study to explore the accessibility and prospective acceptability of videoconference-mediated psychological therapy with people with an ID. This evaluation is in line with the growing need of involving individuals with ID in decisions regarding their own care (Mattock, Beard & Baddeley, 2020).…”
Section: Introductionsupporting
confidence: 57%
“…Similarly, in non-western cultures, people with intellectual disabilities have to deal with stigma and process their emotional reactions in relation to their interactions with family members and mental health professionals. This may negatively affect their sense of self and contribute to feelings of loneliness as described by Robinson et al (2016) and Mattock et al (2020), who found the negative impact of stigma on self-esteem and self-identity of individuals with intellectual disabilities in western cultures. The participants in the current study described how they attempt to reconstruct their self-identity through various means, such as being a supportive friend or carrying out acts of service to help others in the hospital, which also helps to alleviate their boredom and improve their self-esteem (Taua et al , 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The personal qualities of mental health professionals have an impact on the relationships and interactions with this population who prefer mental health professionals who are willing to take time to listen and understand them and help them to promote their competency (Lloyd et al , 2013; Mattock et al , 2020; Stenfert Kroese et al , 2013). This was also found in previous research, people with intellectual disabilities are frustrated with the limited amount of time with their health-care professionals during which their concerns are not adequately addressed (Wilkinson et al , 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Evans and Randle-Phillips (2020) found positive feelings towards the therapist, feeling listened to and valued and feeling it was collaborative were important. “Being heard” has also been identified as being significant, as individuals with an ID often felt like their views were not heard (Mattock et al , 2020). Cameron et al (2020) found that individuals with ID responses to semi-structured interviews validated the alliance dimensions of Bordin’s model.…”
Section: Mental Health In Individuals With Intellectual Disabilitiesmentioning
confidence: 99%